2014
DOI: 10.1177/1060028014526362
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Medication Nonadherence on Glycemic Control

Abstract: In patients with type 2 diabetes, glycemic control worsens over time in the presence of medication nonadherence. Future studies need to take into account the complexity of patient- and system-level factors affecting long-term medication adherence to improve diabetes-related outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 28 publications
1
108
0
3
Order By: Relevance
“…On the other hand, the decline in MPR observed in patients with more severe or advanced cancers may be considered clinically important. Interestingly, previous studies showed that a relatively small change in MPR is associated with changes in metabolic control [6,7]. In one study, a statistically significant 48% decrease in the odds of poor glycaemic control (HbA 1c >8% (64 mmol/mol)) was found for each percentage increase in MPR (OR 0.5; 95% CI 0.4, 0.6) [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the decline in MPR observed in patients with more severe or advanced cancers may be considered clinically important. Interestingly, previous studies showed that a relatively small change in MPR is associated with changes in metabolic control [6,7]. In one study, a statistically significant 48% decrease in the odds of poor glycaemic control (HbA 1c >8% (64 mmol/mol)) was found for each percentage increase in MPR (OR 0.5; 95% CI 0.4, 0.6) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Achievement of normal or near normal glycaemia (HbA 1c goal of <7% [53 mmol/mol] [5]) in individuals with diabetes is strongly linked with adherence to medication regimens [6,7]. Overall, only 65-85% of GLD users are regarded as adherent [8,9]; this might decrease even more after a diagnosis of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline A1c values were obtained through a fingerstick blood sample taken during the enrollment interview. 19 Pre-enrollment clinic A1c levels were used if this value was missing [n=29 (10 %)]. Height, weight and blood pressure were measured at the initial visit.…”
Section: Methodsmentioning
confidence: 99%
“…This, in turn, may result in higher glycosylated hemoglobin (A1c) values, as medication adherence, in and of itself, is associated with and predictive of glycemic control. 18,19 The purpose of this study is to evaluate the relationships between food insecurity and depression, diabetes distress and medication adherence, and to determine whether these factors are part of the pathway between food insecurity and glycemic control. A better understanding of the relationship between food insecurity status and diabetes control may identify new intervention targets for patients with poorly controlled diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…21 22 We also considered medication status (receipt versus non-receipt of prescription for diabetes medication during the study period) and service-connected disability as a dichotomous (<50%, ≥50%) proxy variable to measure copay status, as has been done in multiple prior studies. 17,[23][24][25] Outcome measure…”
Section: Primary Covariatesmentioning
confidence: 99%